Tik tok as a digital pedagogical tool for vocal music instruction: a case study of unisono singing in secondary education - Muhammad Fachrurozi Aliva; Syeilendra Syeilendra; Indrayuda Indrayuda; Jupriani Jupriani (Global Econedu, 2026)
This qualitative case study examines how TikTok was implemented as a learning medium for unisono singing instruction in an Arts and Culture class at a laboratory secondary school affiliated with a state university in West Sumatra, Indonesia. The study explored changes in students’ motivation after the platform was introduced and examined students’ perceptions of this new learning channel. Digital environments increasingly bridge traditional music education practices and the learning preferences of digitally native students, yet detailed accounts of how short-form video applications are integrated with culturally grounded vocal instruction at the secondary level remain scarce, particularly outside Western and higher-education contexts. Data were gathered through classroom observation across four sessions, semi-structured interviews with the teacher and five purposively selected twelfth-grade students, and a portfolio of instructional materials and student videos. Data were analyzed following Miles, Huberman, and Saldaña’s interactive model of data condensation, display, and conclusion drawing/verification, with credibility strengthened through triangulation across sources and methods. Findings show that TikTok was integrated across three instructional stages planning, execution, and assessment functioning as a reference library, a rehearsal aid, an assignment channel, and a feedback and showcase tool. Students’ engagement increased through self-paced, repeated practice, reflecting constructivist and scaffolded learning principles, and their view of TikTok shifted from entertainment toward a legitimate pedagogical resource, although distraction and camera-related self-consciousness remained challenges requiring active teacher mediation. These findings suggest that a culturally grounded combination of traditional vocal pedagogy and short-video technology offers transferable insights that remain underexplored in secondary arts education.